Istri Bekerja di Pesantren: Pelaksanaan Hak dan Kewajiban dalam Keluarga - Fa'atirahmah, Raden Rara Lisa (Jurnal Wanita dan Keluarga, 2025)
This study aims to analyze how career women working as teachers at PPTQ SahabatQu balance their rights and responsibilities in both domestic and public sectors. Additionally, it examines the roles of husbands and wives in facilitating this balance and explores the Islamic legal perspective on the fulfillment of these rights and responsibilities. This research employs a qualitative approach with a descriptive-analytical method. Primary data was collected through in-depth interviews with four married teaching couples at PPTQ SahabatQu. The data was analyzed using thematic analysis to identify patterns of interaction and strategies for balancing roles. The findings indicate that career women face challenges in managing their time, energy, and dual responsibilities. To maintain balance between professional and domestic roles, couples adopt strategies such as intensive communication, negotiation with their spouses, delegation of household tasks, and an Islamic law-based understanding of gender role flexibility. The implementation of career women's rights and responsibilities within the pesantren environment aligns with Islamic principles. However, improvements in communication and role distribution are still necessary to prevent imbalances in household responsibilities.